Does author affiliation reputation affect uncitedness?. Issue 1 (24th February 2016) - Lou, Wen; He, Jiangen
ABSTRACT: This study analyzes the relation between author affiliation reputation and uncitedness. We use 2015 U.S. News Best Global University Subject rankings as representative of affiliation reputation and collect uncited papers from 24 journals in six subjects from WoS. Preliminary correlation analysis results indicate that: (1) there is a significant correlation between affiliation reputation and uncitedness. (2) their relation is negatively and weakly correlated. And secondary data collection and correlation analysis proved that relation between affiliation reputation and uncitedness vary in different subjects. The findings of this study would attract scientists' attention to avoid Matthew Effect and focus more on research papers rather than reputation when citing references.